Eco-Politics in James Hilton’s Lost Horizon - Shwana Qadir Perot (QALAAI ZANIST JOURNAL, 2021)
Eco-criticism as a newly emerged theory pays attention to environmental issues. It aims to grow awareness about the planet and identifies factors damaging nature. James Hilton in his famous utopian novel Lost Horizon notifies human beings of the horrific consequences of war and other violent actions. He draws the reader’s attention to a world which is on the brink of destruction due to the war and its aftermath. On the other hand, he creates a harmonious society for the war-weary people who flee their places due to the political tensions. Throughout the novel, Milton expresses his anger toward the politicians who have put life and nature at stake. As nowadays, the trench of warfare has exceeded human miseries; it has resulted in several environmental problems. This article aimed to examine the novel and its depiction of the horrors of war from an ecocritical perspective. Hilton’s novel, as an eco-fictional work, demonstrated an apocalyptic world dominated by horrors of war. On the other hand, it also demonstrated a tranquil world which is free of war and natural destruction.